Letter (copy) : Spain - Citrine, Walter, 1887-1983
011-0057-001 WMC/EAB/1117 International 23rd August 1937. Mr. G. Stolz, International Federation of Trade Unions, 9, Avenue D'Orsay, PARIS. VII. Dear Comrade Stolz, SPAIN, I have your letter of the 20th instant and note the communications which have passed between yourself and Comrade Caballero regarding the request by the Executive of the Spanish U.G.T. for the convocation of an extraordinary I.F.T.U. General Council Meeting. I am in complete agreement with the reply you have sent to our Spanish comrades, as I think the onus is upon them to show clearly what could be accomplished by such a meeting. Our greatest desire is to do everything possible to assist our Spanish comrades in their struggle, but I do feel that a request for a special meeting of the General Council should be accompanied by an indication of the particular points which it is desired such a meeting should consider. Yours sincerely, General Secretary. 292/946/11/57